Nonlinear model-based control of combustion timing in premixed charge compression ignition. (June 2014) - Kocher, Lyle E; Hall, Carrie M; Van Alstine, Dan; Magee, Mark; Shaver, Gregory M
One of the major challenges in the control of advanced combustion modes, such as premixed charge compression ignition, is controlling the timing of the combustion event. A nonlinear model-based controller is outlined and experimentally shown to be capable of controlling the engine combustion timing during diesel premixed charge compression ignition operation on a modern diesel engine with variable valve actuation by targeting the desired values of the in-cylinder oxygen mass fraction and the start of injection. Specifically, the experimental results show that the strategy is capable of controlling the start of combustion and the intake oxygen mass fraction to within 1° crank angle and 1% respectively. A stability analysis also demonstrates that this control strategy ensures asymptotically stable error dynamics.